MODEL-BASED DEVELOPMENT OF ENGLISH LANGUAGE LEARNING CHARACTERS IN IMPROVING STUDENTS ACHIEVEMENT OF SMA - Sariakin Sariakin (SCAD Independent, 2016)
The purpose of this study is to discover, describe and explain the development model of character-based English language in senior high schools to improve student’s achievement. This study is designed to approach research and development, the research is followed up by studying, investigating, and understanding as well as how the model-based development of English Language learning character develop. The sample of the study consists of 30 teachers who are taken from 8 senior high schools in Banda Aceh that have the same background and characteristics. To produce a model of teaching English in senior high schools in Banda Aceh, the model is conducted systematic steps in the form of the process of action, reflection, evaluation, and innovation. The method used is direct observation, questionnaires, interviews, seminars, and development. Furthermore, this research is expected to produce English language-based learning model character in accordance with the national culture.